Physical exercise and psychological well being: a critical review. Issue 2 (June 1998) - Scully, D; Kremer, J; Meade, M M; Graham, R; Dudgeon, K
Abstract : The relation between physical exercise and psychological health has increasingly come under the spotlight over recent years. While the message emanating from physiological research has extolled the general advantages of exercise in terms of physical health, the equivalent psychological literature has revealed a more complex relation. The paper outlines the research evidence, focusing on the relation between physical exercise and depression, anxiety, stress responsivity, mood state, self esteem, premenstrual syndrome, and body image. Consideration is also given to the phenomena of exercise addiction and withdrawal, and implications for exercise prescription are discussed.